Interfacial Transport Study of Ultra-Thin InN-Enhanced Quantum Dot Solar Cells - Shuaijie Wang; Dong Zhang; Zhenhe Ju (Advances in Materials Science and Engineering)
For human society, all activities require energy support. Solar cells are a means of converting solar energy into electrical energy using the photovoltaic effect of semiconductor materials. This photoelectric absorber layer has been developed for more than 70 years. Currently, the layered solar panel industry has achieved an energy conversion efficiency of 47%. In addition to efficiency, the cost of solar cells has been optimized, and the cost of commercial silicon solar cells has been greatly reduced. There is an urgent need for energy transfer research through the solar cell interface. Many researchers are studying and discovering new elements in this field. On this basis, the transmission ion interface of ultra-thin in-amplified quantum solar cell panels was studied, and very effective conclusions were drawn on the basis of experimental preparation and analysis.